Penerapan Model Pembelajaran Kooperatif Tipe Make A Match Untuk Meningkatkan Hasil Belajar Siswa Kelas IV Di MI Miftahul Ulum Betiting Cerme Gresik - Isnatil Fadhila; Ainul Fitriyah; Nurul Agustin; Ria Resti Fauziah; Muhammad Luthfi Efendi; Rahmat Rudianto (Konsorsium Pengetahuan Innoscientia (KOPINNOS), 2026)
The Make a Match cooperative learning model is an innovation of the cooperative learning model that emphasizes collaboratively finding pairs of question and answer cards to create an active and enjoyable learning atmosphere. The problem of this research is the low learning outcomes and activeness of fourth-grade students at MI Miftahul Ulum Betiting Cerme Gresik due to teacher-centered learning. This study aims to improve student learning outcomes through the application of the Make a Match model. The method used is Classroom Action Research (CAR) in two cycles which include the planning, implementation, observation, and reflection stages. The research subjects were 20 students in the 2024/2025 academic year. Data collection techniques used tests, observations, interviews, and documentation, then analyzed descriptively quantitatively and qualitatively. The results showed an increase in the average score from 60.5 in the pretest to 72.0 in cycle I and 82.4 in cycle II. The percentage of learning completeness increased from 10% to 50% and reached 85%. Thus, the Make a Match model is effective in improving student learning outcomes, participation, and interaction.